Teachers in Specialized Education Support Services: Responsibilities and Impossibilities - Castro, Juliana Telles de; Vaz, Alexandre Fernandez (Education Policy Analysis Archives, 2015)
This paper presents some results of a research that investigated inclusion process of a Multimedia Room of Specialized Education Support Services offered at the public school in Florianopolis, Brazil. We analyzed the contents of two documents and conducted a series of observations and interviews. The results show certain teaching divestment. Teachers are largely relegated to their own initiative to develop and implement inclusion strategies. This seems to be done both under the Zeitgeist of educational policies, but also the usually expectations to teachers in modern pedagogical tradition. It reveals an impossibility of inclusive processes.